Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-68835
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Investigation of a Nozzle Clearance Effect on Radial Turbine Performance

Abstract: Liebherr Aerospace designs and develops cooling air systems, with notably axial fan and radial turbine or compressor. The development of new architectures (especially electrical system) now requires improving the turbine performances on the whole operating range. To reach that industrial request, a variable nozzle area can be used, performed by changing the nozzle blade angle for a given blade height. For the blades to be moveable, tip and hub clearances must be present (and thus modeled) in the nozzle. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These flow losses are partly responsible for the decrease in turbine efficiency due to nozzle endwall clearance. The work of Roumeas and Cros [3] also indicated that the clearance leakage leads to the development of vortices along the nozzle vane chord that tends to increase the total pressure loss in the nozzle. Natkaniec et al [11] performed a numerical research of secondary flow structures and losses in a turbine with realistic vanes and found that some typical vortices generate a lot of flow loss in stator.…”
Section: Shock Wave In Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…These flow losses are partly responsible for the decrease in turbine efficiency due to nozzle endwall clearance. The work of Roumeas and Cros [3] also indicated that the clearance leakage leads to the development of vortices along the nozzle vane chord that tends to increase the total pressure loss in the nozzle. Natkaniec et al [11] performed a numerical research of secondary flow structures and losses in a turbine with realistic vanes and found that some typical vortices generate a lot of flow loss in stator.…”
Section: Shock Wave In Turbinementioning
confidence: 99%
“…This leakage flow is restricted to the pressure side, due to the pressure gradient towards the inner radius from the outer radius of the nozzle, and flows out while forming endwall leakage vortices along the nozzle surface. Roumeas and Cros [3] did an investigation about the inception and development of nozzle clearance leakage vortices and pointed out that there are three different causes which are responsible for turbine efficiency loss: the total losses induced by vortex, the changed incidence angle distribution, and a shifting in operating points.…”
Section: Introductionmentioning
confidence: 99%
“…The mesh size is around eleven million points and ensures that y + values are strictly lower than five. For more details about the turbine geometry and the whole numerical set up considered, see Roumeas and Cros [19].…”
Section: Test Casesmentioning
confidence: 99%
“…The mesh size is around eleven millions points and ensures that y + values are strictly lower than five. For more details about the turbine geometry and the whole numerical set up considered, see Roumeas and Cros (2012).…”
Section: Test Casesmentioning
confidence: 99%